Automatic detection of underground utility using Ground Penetrating Radar (GPR) dataset / Warishah Abdul Wahab - Abdul Wahab, Warishah (Institute of Graduate Studies, UiTM, 2018)
Complete and accurate information regarding subsurface material such as underground utility is becoming increasingly important nowadays. With the right information and updates on the underground utility such as location, type, depth and material; catastrophic events such as underground utility damage caused by miss digging and disruption to existing utility services can be avoided or at least minimised. Based on the study, Ground Penetrating Radar (GPR) is one of the latest nondestructive geophysical technology and most widely used in detecting underground utilities. GPR has the ability to detect both metal and nonmetal, however, it is unable to identify the type of underground utility object. Many researchers come out with their own techniques to interpret the GPR image. The current method requires experience in interpretation. Thus, in this study, a new method to detect underground utility by utilising the Normalised Cross Correlation (NCC) template matching technique is proposed. This technique will reduce the dependency on experts to interpret the radargram, less time consuming and eventually save cost. Upon detection, the accuracy of the system is assessed. From the accuracy assessment performed, it is shown that the system provides accurate detection results for both, depth and pipe size…